ANALYSIS OF THE USE OF SPELLING AND VOCABULARY IN THE ESSAY DESCRIPTION OF GRADE IV ELEMENTARY SCHOOL STUDENTS (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2018)
Writing skills are the last skills mastered after listening, speaking and reading skills. In the digital era, students can access various types of writing through various media such as mobile phone. This research was conducted to find out the skill of writing essays description about technological equipment in the digital era. The researcher gave a test writing essay description of mobile phones in class IV public elementary schools in the city of Surakarta, Central Java. The description desk is reviewed from an analysis of the use of spelling and vocabulary. The method used in this study is qualitative descriptive. The results showed that there were still many students who did not pay attention to the use of spelling in writing. Spelling use errors especially in the use of capital letters, use of a dots and commas, and writing absorption words. The vocabulary used by most students is a non-standard word. The use of a second language also influences students' essays. Thus, it can be concluded that the skills of fourth grade students in writing description essays are still low.